2020
DOI: 10.12982/vis.2021.022
|View full text |Cite
|
Sign up to set email alerts
|

The comparatives of growth and carcass performance of the Thai native chicken between economic selection (Chee KKU12) and natural selection (Chee N)

Abstract: Chee is 1 of 4 important native chicken breed in Thailand. Genetic selection can be used to improve growth and carcass performance. The objective of this study was to compare growth and carcass performance of native chickens (Chee) with a population selected for economic traits (Chee KKU12) and natural selection (Chee N). Two hundred Chee KKU12 and Chee N chickens were divided into 5 replicates, 20 chickens per replication. Record growth and carcass quality for data analysis. The results showed that at 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…For this reason, KKU1 chickens can answer this question better than commercial broilers. However, the body weight of the KKU1 and KKU2 chickens was shown to be significantly higher compared to purebred and other crossbred indigenous chickens, while when compared to other Thai indigenous breeds, such as Chee chickens (Chee KKU12 and Chee N) [1,19], it was found to be two times higher at 6 weeks of age. In addition, when considering only KKU1 chickens, it was found that they had a higher body weight than Lueng Hang Kao Kabinburi Thai indigenous chickens [12].…”
Section: Discussionmentioning
confidence: 76%
“…For this reason, KKU1 chickens can answer this question better than commercial broilers. However, the body weight of the KKU1 and KKU2 chickens was shown to be significantly higher compared to purebred and other crossbred indigenous chickens, while when compared to other Thai indigenous breeds, such as Chee chickens (Chee KKU12 and Chee N) [1,19], it was found to be two times higher at 6 weeks of age. In addition, when considering only KKU1 chickens, it was found that they had a higher body weight than Lueng Hang Kao Kabinburi Thai indigenous chickens [12].…”
Section: Discussionmentioning
confidence: 76%
“…Our researchers have improved their genetic growth performance since 2002. However, HB has a small size with a slow growth rate, and its ability to grow is limited; the matured weight was reported to be range approximately from 1250 to 1550 g [40][41][42][43]. The negative values in HB indicate that the growth genetics were not affected by their growth.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Guni et al [ 24 ] found that at 20 weeks of age, Kuroiler and Sasso chickens (exotic breeds) raised in the testing station had higher body weights (2313.1 and 2708.8 g, respectively) than those raised on the farm (1995.2 and 1745.9 g, respectively). However, a comparison of the body weight of the native chickens in this study with that of other Thai native chickens showed that the chickens in this study had body weights 122 g higher than that of Chee chickens [ 9 ] and 88 g higher than that of Leung Hang Khao chickens [ 13 , 14 ]. In addition, the body weights were higher than those of native chickens in Korea [ 25 ], chicken strains in Egypt [ 26 ], Venda chickens of South Africa [ 29 ], and native chickens of Ethiopia [ 30 ].…”
Section: Discussionmentioning
confidence: 95%
“…The main advantages of native chickens are that they are easy to raise and well adapted to local conditions, especially to the use of local feed source, and have an excellent ability to resist disease and poor weather compared to exotic chicken breeds [ 5 , 6 ]. From a marketing perspective, native chicken meat has proven itself in many ways, such as its distinct taste and flavor [ 7 ], and is used as a health food because of its low cholesterol [ 8 ] and high nutritional components [ 9 , 10 , 11 ], which are essential human health considerations. Therefore, native chicken meat has created a rapidly increasing demand in the chicken market for consumers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%